Perkembangan Penelitian Artificial Intelligence Dalam Pendidikan Matematika Sekolah Dasar: Tinjauan Literatur Sistematis - Nila Khoirotun Ni’mah; Dea Adinda Febrianti; Naura Yumna Nadhifa; Syalwa Revalanisa Putri; Felya Octaprianti; Najwatul Aqilah (Prosiding Konferensi Ilmiah Dasar, 2026)
The rapid development of Artificial Intelligence (AI) has transformed mathematics education by enabling more adaptive, personalized, and data-driven learning. However, systematic evidence on AI implementation specifically at the elementary school level remains limited. This study analyzes research trends, technologies used, contributions, and challenges of AI in elementary mathematics education through a Systematic Literature Review following PRISMA 2020 guidelines. Literature was retrieved from Google Scholar and screened using predefined inclusion and exclusion criteria, yielding 32 eligible articles published between 2020 and 2024, analyzed through narrative synthesis. Findings show a growing research trend, with ChatGPT, Gemini, Intelligent Tutoring Systems, Adaptive Learning, Learning Analytics, and Machine Learning as the most frequently used technologies. AI implementation improves conceptual understanding,learning achievement, motivation, engagement, and Higher Order Thinking Skills(HOTS). However, teachers' digital competence, technological infrastructure, digital literacy, and ethical and data security issues remain major barriers.